ASSOCIATION BETWEEN FASTING BLOOD GLUCOSE AND C-REACTIVE PROTEIN LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS - Devi, Komang Ayu Aishvarya Gangga; Sewar, Caroline Ester; Krisna, Luh Ade Wilan; Rakhmawati, Aprilia (Meditory : The Journal of Medical Laboratory, 2025)
Background: Diabetes mellitus (DM) is characterized by elevated blood glucose levels resulting from decreased insulin secretion by pancreatic beta cells. Fasting blood glucose (FBG) measurement is commonly used to monitor DM, requiring patients to fast for a minimum of eight hours. Insufficient insulin production impairs glucose uptake into body tissues, leading to hyperglycemia. Chronic hyperglycemia subsequently stimulates the production of inflammatory cytokines, which promotes the hepatic synthesis of C-reactive protein (CRP).Objective: This study aims to determine the relation between FBG and CRP levels in patients with type 2 diabetes mellitus (T2DM) at Mangusada Hospital.Method: An observational analytic study was conducted using purposive sampling, with a total sample of 25 T2DM patients.Result: The lowest FBG level was 126 mg/dL, while the highest was 319 mg/dL. The lowest CRP level was 0.2 mg/L, whereas the highest was 23.7 mg/L. High FBG and CRP levels were observed in 44% of respondents, while high FBG with normal CRP levels were found in 56%. The highest FBG (319 mg/dL) also exhibited the highest CRP level (23.7 mg/L) The non-parametric Spearman’s rank correlation revealed a significant association between FBG and CRP levels with p-value of 0.012 (0.05) and r = 0.493 indicated a positive and moderate correlation.Conclusion: There is a positive, moderate correlation between FBG and CRP levels in T2DM patients at Mangusada Hospital. KeywordsC-Reactive Protein, blood glucose, diabetes